ИЗВИЦИТЕ ВО ЌОПИЌЕВИТЕ ПРИКАЗНИ ЗА ДЕЦА НА МАКЕДОНСКИ ЈАЗИК (Philological Studies, 2019)
We have chosen the subject interjections in Ćopić’s novels for children in Macedonian language having in mind few reasons: 1. Branko Ćopić is one of the most famous writers for children in former Yugoslavia; 2. From the sociolinguistic point of view, regardless of the fact that his books had been translated into many languages (Russian, Ukrainian, Polish, Czech, Bulgarian, Hungarian and German), the books translated into Macedonian language are not many, which is a rarity for us; 3. The interjections, as a special word class, are a subject of discussion in the modern researches regarding their classification, as well as regarding their functional-semantic realization; 4. Analysis of the interjections in the novels translated in the fifth decade of the 20th century indicates the synchronic frame of the Macedonian language in that period of time; 5. From the stylistic point of view, Branko Ćopić is a writer who is using the interjections very often, not only in his works, but also in his linguistic (personal) style. The interjections found in the 22 analyzed novels in Macedonian were put in alphabetical order and, generally, in three groups: interjections expressing feelings, interjections calling someone, establishing contact and interjections used to imitate sounds. The executed scientific research has justified the reasons taken into consideration for choosing this actual subject.
Keywords: Macedonian language, interjections, Ćopić’s novels